Tunable Plasmonic Perfect Absorber for Hot Electron Photodetection in Gold-Coated Silicon Nanopillars - Tangyou Sun; Wenke Song; Zubin Qin; Wenjing Guo; Peihua Wangyang; Zhiping Zhou; Yanrong Deng (Photonics, 2023)
Infrared detection technology has important applications in laser ranging, imaging, night vision, and other fields. Furthermore, recent studies have proven that hot carriers which are generated by surface plasmon decay can be exploited for photodetection to get beyond semiconductors’ bandgap restriction. In this study, silicon nanopillars (NPs) and gold film at the top and bottom of silicon nanopillars were designed to generate surface plasmon resonance and Fabry–Perot resonance to achieve perfect absorption. The absorption was calculated using the Finite Difference Time Domain (FDTD) method, and factors’ effects on resonance wavelength and absorption were examined. Here we demonstrate how this perfect absorber can be used to achieve near-unity optical absorption using ultrathin plasmonic nanostructures with thicknesses of 15 nm, smaller than the hot electron diffusion length. Further study revealed that the resonance wavelength can be redshifted to the mid-infrared band (e.g., 3.75 μm) by increasing the value of the structure parameters. These results demonstrate a success in the study of polarization insensitivity, detection band adjustable, and efficient perfect absorption infrared photodetectors.